FAKTOR-FAKTOR SEBAGAI PERTIMBANGAN KONSUMEN DALAM MELAKUKAN PEMBELIAN DI SUPERMARKET - Cahyono, Yuli Tri (Benefit, 2008)
The impact of supermarkets (including hypermarkets) on the existence of traditional markets has recently become a topic of heated public debate. According to anumber of circles, the traditional markets are the most affected by the impact of competition from the supermarkets. Many people believe that the presence of modern markets, especially supermarkets and hypermarkets, is pushing urban traditionalmarkets into a corner. The superiority of modern over traditional markets lies in the fact that the former can sell the same products at lower prices, in addition to the comfort and different payment options they offer shoppers. Furthermore, the supermarkets and hypermarkets establish business links with large suppliers, usually for an extended period of time. This enables them to operate efficiently, benefitting fromthe economies of scale. Supermarkets adopt a number of pricing and non-pricing strategies to attract customers such as price limits, predatory pricing, and intertemporal price discrimination, for example, discounts at the end of the week and at certain other times. Their non-pricing strategies include advertising, longer opening hours (especially on weekends), bundling or tying (combined purchases), and free parking.